Análisis socio jurídico de la falta de medidas para la reinserción y seguimiento de un niño niña o adolescente (NNA) luego de ser separado de su lugar de explotación laboral en la ciudad de Machala en el año 2012-2013 propuesta de reforma al capitulo IV del titulo V del libro I del código de la niñez y la adolescencia. - Flores Barba, Félix Javier (2015)
Girls, children and teens, music I join of them group of priority attention than you find yourself in the hurricane's eye all over the world in the present-day moments, since his rights consecrated in the law and universal declarations go away more and more damaged for the citizens, since for cultural and social features they do not enable the integral development of this group of priority attention forcing them to obey adults' tasks. Our juridical labor and childhood organizing and the young people adopt one without number of destined standards to the protection of the rights of the children, girls and teens referring to the labor field, having like our baseline constitution promulgated in the year 2008 the same than not only that garantista than the constitution of 1998. Our investigation does the same split with a host question that Existen measured of re-insertion for the children is girls and teens recovered of centers of labor exploitation?, Right after investigation and the normative comparison, you get along well than exists a vacuum referring to this type of measures that is necessary and a substantial change referring to the re-insertion of the children, girls and teens. We have to have under consideration than so much Erradicación's program of the Child Labor of the Department Of Labor like the Inspectors of work and the Judges of Familia's Units, woman, childerns, adolescence and adolescent infringers of our city and of the country, they try to embrace in his great majority the standards for the fulfillment and you safeguard of this vulnerable group like music minors, but they look limited by the lack of ground rules in regard to this theme and many times his I work they look truncate why he is not given a tracking due to the children's re-insertion girls and teens and his progress in the society. Definitively a substantial reform to the juridical standards is necessary that the children's re-insertion, girls and teens establish that they be recovered of the labor investment centers.